How warm was Britain during the Last Interglacial? A critical review of Ipswichian (MIS 5e) palaeotemperature reconstructions. (November 2016) - Candy, Ian; White, Tom S.; Elias, Scott
ABSTRACT: The Last Interglacial [LIG, equivalent to marine isotope stage (MIS) 5e] was a period of enhanced global warmth, with potential significance for understanding future climate warming. It has long been proposed that the LIG in Britain (the Ipswichian Interglacial) was significantly warmer than present, based on the occurrence of fossils of extant thermophilous plant and animal species intolerant of the current climate. Here, we review the evidence for palaeotemperatures that can be derived from such fossil taxa (beetles, ostracods, plant macrofossils and herpetiles) to assess the level of warmth that Britain experienced during the LIG. Quantified palaeotemperature reconstructions generated for eight British sequences indicate that the LIG was likely to have been warmer than the present but at only one site (Trafalgar Square) is there strong evidence for climates that were significantly warmer than those experienced during the Holocene. Consequently, while there is evidence to support the idea that the thermal regime of the LIG in Britain was different from that of the Holocene, this evidence is restricted to a single site. The paper concludes by discussing the thermal regime of the LIG in Britain in the context of its role as an analogue for future warming in the 21st century and beyond.